Raw Fragment Analysis Data - Rando, Halie; Stutchman, Jeremy T.; Bastounes, Estelle R.; Johnson, Jennifer; Driscoll, Carlos; Barr, Christina; Trut, Lyudmila N.; Sacks, Benjamin N.; Kukekova, Anna V. (Dryad Digital Repository, 2017)
This is all of the raw data generated and analyzed for the development of a 13-microsatellite marker panel for the red fox Y-chromosome. It may be useful to researchers looking to calibrate calls made in new samples/populations using these markers. This zipped file includes all original .abi files, raw allele calls and peaks as produced with GeneMapper v3.5, a table of the final allele assigned to each individual at each marker, and the .ych file used to construct the haplotype network in Figure 2 with Network 5.0.0.0.